Japan's killer quake [videorecording (DVD)] (PBS Home Video, 2011)
In its worst crisis since World War II, Japan faces disaster on an epic scale: a rising death toll in the tens of thousands, massive destruction of homes and businesses, shortages of water and power, and the specter of nuclear reactor meltdowns. It combines on-the-spot reporting, personal stories, compelling eyewitness videos, and exclusive helicopter footage for a unique look at the science behind the catastrophe.